The Composition of Adipose-Derived Regenerative Cells Isolated from Lipoaspirate Using a Point of Care System Does Not Depend on the Subject’s Individual Age, Sex, Body Mass Index and Ethnicity - Schmitz, Christoph; Alt, Christopher; Azares, Alon R.; Pearce, David A.; Facile, Tiffany R.; Furia, John P.; Maffulli, Nicola; Huang, Claire; Alt, Eckhard U. (Cells (Basel, Switzerland), 2022)
Uncultured, unmodified, autologous, adipose-derived regenerative cells (UA-ADRCs) are a safe and effective treatment option for various musculoskeletal pathologies. However, it is unknown whether the composition of the final cell suspension systematically varies with the subject’s individual age, sex, body mass index and ethnicity. UA-ADRCs were isolated from lipoaspirate from n = 232 subjects undergoing elective lipoplasty using the Transpose RT system (InGeneron, Inc.; Houston, TX, USA). The UA-ADRCs were assessed for the number of nucleated cells, cell viability and the number of viable nucleated cells per gram of adipose tissue harvested. Cells from n = 37 subjects were further characterized using four-channel flow cytometry. The present study shows, for the first time, that key characteristics of UA-ADRCs can be independent of the subject’s age, sex, BMI and ethnicity. This result has important implications for the general applicability of UA-ADRCs in regeneration of musculoskeletal tissue. Future studies must determine whether the independence of key characteristics of UA-ADRCs of the subject’s individual age, sex, BMI and ethnicity only applies to the system used in the present study, or also to others of the more than 25 different experimental methods and commercially available systems used to isolate UA-ADRCs from lipoaspirate that have been described in the literature.